2022
DOI: 10.32641/andespediatr.v93i1.3619
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome de ACNES, explorando la pared abdominal como noxa del dolor abdominal

Abstract: El dolor de pared abdominal, y concretamente el síndrome de ACNES (Anterior Cutaneous Nerve Entrapment Syndrome), forma parte del diagnóstico diferencial del dolor abdominal crónico. Este síndrome es poco conocido y por consiguiente infradiagnosticado. Objetivos: Describir las características clínicas y evolutivas de pacientes diagnosticados de ACNES y llamar la atención sobre esta patología. Pacientes y Método: Estudio descriptivo retrospectivo realizado en un centro de referencia, entre octubre 2016 y julio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…One study, by García et al [ 21 ], reported on conservative treatment for ACNES. Seven of the twenty patients (35%) reported improvement after oral medication, while one patient reported spontaneous improvement.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One study, by García et al [ 21 ], reported on conservative treatment for ACNES. Seven of the twenty patients (35%) reported improvement after oral medication, while one patient reported spontaneous improvement.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, fve case series (108 patients) and two case reports (2 patients) reported on surgical procedures, and one study detailed outcomes after both injections and surgical interventions (12 patients). Only one article described the results of conservative noninvasive treatment [21]. Among the 11 case series, six originate from the same surgical research group, accounting for 74% of all patients [5,20,[22][23][24][25].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations